STAKE EVALUATION MODEL (COUNTENANCE MODEL) IN LEARNING PROCESS BAHASA INDONESIA AT GANESHA UNIVERSITY OF EDUCATIONAL - Dewantara, I Putu Mas (International Journal of Language and Literature, 2017)
The evaluation study aimed to describe the implementation of Bahasa Indonesia as character development subjectÂ  (Matakuliah Pengembangan Kepribadian/MPK) seen from (1) the learning plan, (2) the implementation of learning, and (3) evaluation of learning. Evaluation model used was a stake evaluation model (Countenance Model). Data were analyzed by descriptive-quantitative. The data were collected by using questionnaire, interview, and documentation. Categorization percentage is divided into five criteria, namely excellent (> 80%), good (60%-80%), fairly good (40%-60%), poor (20%-40%), and very poorly (<20%). The research was conducted in the first semester of the academic year 2015/2016 with the sample of 315 students. The results showed that in general the Bahasa Indonesia as character development subject was categorised as good with the percentage of 71.02%, in detail, the result can be described as follows: (1) the learning plan is categorized as good with the percentage of 72.62%, (2) the implementation of learning is categorized as good with the persentage of 69.85%, and (3) evaluation of learning activities is categorized as good with the persentage of 70.59%. The implications of this research for lecturers is a need for efforts to sustain the implementation of learning that has been good even working on improving and working to improve elements of learning activities that have not been considered good. The results of the study suggest that regular evaluation needs to be done to get a better picture of evaluation with a larger number of sample. Another suggestion that can be proposed is the evaluation of learning by using a variety of evaluation model to get a better result of the learning Bahasa Indonesia.